Discrete Cosine Transform Algorithm Analysis of The Application of QR Codes on Birth Certificate Image Objects - Fauzi, Achmad (LPPM UNIKA Santo Thomas Medan, 2024)
Security and authentication of important documents such as birth certificates have become a major concern today and in the digital age. In this context, the use of watermarking technology is an effective solution to add additional information to digital documents without destroying their authenticity. The DCT method is used to convert images into the frequency domain, allowing the watermark to be added without disturbing the appearance of the document. Testing ensures that the watermarking process does not damage the appearance of the original document and that the watermark information can be accurately re-extracted. The research results show that the QR code watermark using the DCT method successfully provides secure and authentic birth certificates. The application of the Discrete Cosine Transform (DCT) method to the birth certificate QR code watermarking process was able to significantly improve document security and authentication without compromising document quality or important information. This thesis outlines the extensive steps in the practical application of the QR code watermark on birth certificates. From data preparation including birth certificate images and QR codes to the watermark conversion and extraction process, all steps are explained in detail. Thus, applying this watermarking technique can be an effective solution to protect the integrity of birth certificates and similar documents in the digital environment.